Fine root litter traits of Chamaecyparis obtusa. (September 2022) - Yoshida, Gen; Doi, Ryuusei; Wada, Ryusei; Tanikawa, Toko; Hirano, Yasuhiro
Graphical abstract: Highlights: Fine root litter was collected using a new method in Chamaecyparis obtusa forests. Monthly amounts of fine root litter showed significant differences among the months. Fine root litter with similar morphology is shed in every month. First-order roots were shed at the branching positions or in the middle of roots. Abstract: The purpose of this study was to clarify the process of Chamaecyparis obtusa (Sieb. & Zucc.) Endl. fine root shedding and the morphological traits of the resulting root litter. We developed a method for direct monthly sampling of root litter from the fine root system in the field. We proposed a field incubation method using centrifuge tubes with glass beads as the medium and throughfall as the nutrient solution, in which an undamaged sample of the fine root system still connected to the tree is inserted. Using this method, we collected root litter from C. obtusa for 12 months after the installation. The monthly amounts of the root litter of from the incubated fine root systems differed significantly among the sampling months. On the other hand, the morphological traits such as the root litter length and diameter of each branch order did not differ significantly among months. The first-order root litter was shorter than the incubated living first-order roots. The first-order roots were shed both at the branching positions and in the middle of first-order roots. We concluded that fine root litter with similar morphology is shed every month. Assessment of the fine root litter traits by using the new direct sampling method and the new soil ecological indicator "initial tissue C inputs" from fine roots into forest soil will improve our understanding of forest belowground carbon cycling and its indexation.